2017
DOI: 10.1016/j.jds.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathologic features related to the impacted third molars in patients of different ages: A retrospective study in the Korean population

Abstract: Background/purpose The surgical extraction of impacted third molars (ITMs) is a common surgical procedure in dentistry. If prophylactic removal of ITMs is beneficial, however, is a still disputed issue. The aim of this study was to analysis the pathologic changes in impacted third molars (ITMs) and adjacent teeth according to patient age groups in the Korean population to determine if the prophylactic removal of ITMs is to be supported or not. Materials and methods A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Studies have shown that, 23 the incidence of pathological changes of adjacent M2 due to untreated M3 is only 2.2% in the age group under 20 years old, 7.9% in early 20 years old, 10.0% in late 20 years old, and 32.4% in over 30 years old, 68.1% in over 41 years old. In older patients, impacted M3 can cause irreversible and serious damage to adjacent second molars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that, 23 the incidence of pathological changes of adjacent M2 due to untreated M3 is only 2.2% in the age group under 20 years old, 7.9% in early 20 years old, 10.0% in late 20 years old, and 32.4% in over 30 years old, 68.1% in over 41 years old. In older patients, impacted M3 can cause irreversible and serious damage to adjacent second molars.…”
Section: Discussionmentioning
confidence: 99%
“…In older patients, impacted M3 can cause irreversible and serious damage to adjacent second molars. Therefore, preventive removal of M3 can prevent irreversible damage to some extent 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When age and M3s are considered together, there are several results that cannot be ignored. First, with increasing age, the risk and severity of diseases related to retained M3s increases (Kim, Jee, Song, Kim, & Kim, 2017), and most M3s, including N‐M3s, are removed during one's lifespan (Magraw, Moss, Fisher, Offenbacher, & White, 2016). Second, the prevalence of systemic diseases is higher in elderly individuals than in young individuals, leading to an increased risk of local and systemic complications in M3 extraction surgery (Baensch, Kriwalsky, Kleffmann, & Kunkel, 2017; Chuang, Perrott, Susarla, & Dodson, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Terauchi et al 12 reported that the average age of onset of dentigerous cysts related to ITMs was 45.9±13.3 years. In 2017, Kim et al 13 investigated the development of pathologic conditions in ITMs and the adjacent teeth based on age in Korean patients. They reported that the severity and frequency of pathologic changes in ITMs and second molars due to ITMs increased with age.…”
mentioning
confidence: 99%